LEGAL RESEARCH AGAINST MARRIAGE CANCELLATION DUE TO IDENTITY FALSIFICATION: A Case Study of Sidoarjo Religious Court Decision No. 1213/Pdt.G/2020/PA. Sda - Ni'mah, Farah Firdausi; Suhessyani, Anggrita Esthi (jfpublisher, 2022)
The marriage cancellation can occur because of the decision from Religious Court or District Court. It is caused lack of requirements in a marriage. Under some circumstances a marriage can also be annulled since the stipulation of a court decision which has permanent legal force and is valid since the marriage begins. This research indicated that marriage cancellation occurred due to violation on the provision of Article 72 Paragraph (2) Islamic Law Compilation adds the phrase ‘fraud’ or misunderstanding about husband or wife. In addition, it is strengthened by the existence of defendant who did not ask for a polygamy permit application to the Religious Court as regulated in Article 71 Letter A in Islamic Law Compilation. The legal consequences that derives from marriage cancellation which regulated in Article 28 Paragraph (2) of Law No. 1/1974 concerning marriage. The objective of this research is to analyze the factors of identity falsification caused marriage cancellation and to find out the judge’s consideration in Religious Court Decision with the case No. 1213/Pdt.G/2020/PA.Sda. The method used in this research is juridical-normative. This research analyzed normatively regarding the case of marriage cancellation due to identity falsification. The legal consequent of this marriage cancellation is the born child is still be considered legal. When the plaintiff filed a lawsuit, other defendant’s wife was died. Therefore, the plaintiff and defendant both agreed to cancel their marriage and will legally remarry.